Innovative polymer nanocomposite membranes for industrial applications - Fahim, Irene (AUC Knowledge Fountain, 2015)
The present study aimed at developing novel polymer nanocomposites (PNC) membranes by investigating the different preparation factors (e.g. cross-linking of the membranes, filler type and wt% of the fillers added to the polymers) on the PNC membranes’ properties such as: pore size, permeability, tensile strength, melt flow index, and thermal stability, recorded at different temperatures (ranging from 23 – 60 ºC). The main goal is to have PNC membranes with enhanced tensile properties as well as improved barrier properties which would make PNCS potential candidates for possible industrial application such as packaging, wrapping materials and filtration membranes. Mainly, two polymers were used in this study: Low density polyethylene LDPE as an example of a synthetic polymer, and chitosan (CS) as another example of a natural polymer. In the current research, emphasis was made on the natural polymer due to its biodegradable nature and for proving better performance in concerning its permeability as membrane matrices. PNCS were prepared by mixing each polymer with two nanofillers (graphene and fullerene) with different concentration (0.1, 0.5 and 1wt.%) for studying their influence on the PNCs membrane properties. LDPE ,CS nanocomposite membranes were fabricated by mixing the polymer with graphene (G) and Fullerene (F) nanofillers. Physical cross-linking of CS by sodium tripolyphosphate (TPP) was carried out in order to enhance the binding between the internal CS chains. F and G with different weight percentages (0.1, 0.5 and 1wt.%) were added on physically cross-linked chitosan (CLCS) as well as the non cross-linked chitosan (NCLCS) membranes by wet mixing technique. In the current research, permeability and the pore morphology of the LDPE, CLCS and NCLCS with and without fillers were assessed at room temperature and as a function of increasing the ambient temperature under constant strain. Scanning electron microscopy (SEM) was employed for the evaluation of the fabricated plain and composite membranes structures and pore size, shape and pore size and nanofiller distribution. The average pore sizes were determined using a porosimeter. Validation of the experimental results was conducted using Abaqus/Standard software provided a simulation modelling of steady-state diffusion of the fabricated membranes. The tensile strength and % elongation were also assessed at 25, 30 and 60oC. Response surface methodology (RSM), a statistical analysis tool, was used to determine the optimized mixture for the various factors (temperature, cross-linking of CS, filler type and wt% of the fillers). The results revealed that cross-linking, filler type and filler wt.% play a crucial role in controlling the pore size and accordingly the rest of the physicochemical and mechanical properties of all fabricated LDPE, CS nanocomposite membranes. The pore size of the fabricated LDPE were found to be microporous(0.1-0.2µm) while, CS nanocomposite membranes were found to be in the mesoporous range (i.e. 2-30nm). Moreover, the addition of G and F nanofillers to LDPE, CLCS and NCLCS solutions aided in controlling the CS nanocomposite membranes’ pore size. It enhanced the barrier effect of the membranes by decreasing the pore size. The theoretical modelling results validated the experimental findings, The simulation showed the mass diffusion along the membrane thickness, which could not be calculated experimentally. Increasing the ambient temperature resulted in the decrease in tensile strength due to coarsening of pores upon heating. The optimum membrane conditions were selected according to the membrane's filtration application The RSM results were found to be in agreement with the experimental results, whereby cross-linking of CS, filler type and filler wt.% were significant factors. The factors had a direct influence on the pore size, diffusion time and tensile strength of the PNC membranes. The current research shows that fabricated CS nanocomposite membranes were effective candidates in membrane filtration systems. They could be used for blocking particles such as atmospheric dust, fumes, paint pigments, viruses and bacteria. NCLCS/1wt. % could be used to filter gases. CLCS/1 wt. %F could be used for combustion smoke filtration. LDPE/1 wt. %G could be used for filtration of bromine and lead smoke particles.